Comparative gene expression study between two turmeric (Curcuma longa L.) cultivars - R K Patel, V Ramtekey, A P Bhuriya, D K Ayer, K G Modha, V B Parekh, (Journal of Spices and Aromatic Crops, 2019)
Two turmeric (Curcuma longa L.) cultivars differing in curcumin content viz GNT-2 (4.6 % curcumin) and NDH-98 (1.6% curcumin) were selected for comparative gene expression study in association with total curcumin contents. Sampling was done at six months after planting in open field condition. Differential gene expression patterns were observed between two cultivars by reverse transcription quantitative real time polymerase chain reaction (RT-qPCR), and total curcumin contents were quantified using high performance liquid chromatography (HPLC). Low curcumin yielding cultivar, NDH-98, exhibited higher expression of DCS and CURS3 whereas lower expression of CURS1 and CURS2. However, opposite pattern was observed in a high curcumin yielding cultivar, GNT-2, where DCS and CURS3 expressions were lower but CURS1 and CURS2 expressions were higher. CURS3 showed similar expression between both cultivars. CURS1 and CURS2 expression patterns showed more closer association than DCS and CURS3 gene expression patterns with each other. Differential gene expression patterns could be predictively associated with differential curcuminoids concentrations in turmeric cultivars.